Comparative Proteomic Analysis Provides insight into the Key Proteins as Possible Targets Involved in Aspirin Inhibiting Biofilm Formation of Staphylococcus xylosus - Xu, Chang-Geng; Yang, Yan-Bei; Zhou, Yong-Hui; Hao, Mei-Qi; Ren, Yong-Zhi; Wang, Xiao-Ting; Chen, Jian-Qing; Muhammad, Ishfaq; Wang, Shuai; Liu, Di; Li, Xiu-Bo; Li, Yan-Hua (Frontiers in Pharmacology, 2017)
Abstract: Staphylococcus xylosus is an opportunistic pathogen that causes infection in humans and cow mastitis. And S. xylosus possesses a strong ability to form biofilms in vitro. As biofilm formation facilitates resistance to antimicrobial agents, the discovery of new medicinal properties for classic drugs is highly desired. Aspirin, which is the most common active component of nonsteroidal anti-inflammatory compounds, affects the biofilm-forming capacity of various bacterial species. We have found that aspirin effectively inhibits biofilm formation of S. xylosus by Crystal violet (CV) staining and Scanning electron microscopy (SEM) analyses. The present study sought to elucidate possible targets of aspirin in suppressing S. xylosus biofilm formation. Based on an isobaric tag for relative and absolute quantitation (iTRAQ) fold-change of > 1.2 or < 0.8 (P-value < 0.05), 178 differentially expressed proteins, 111 down-regulated and 67 up-regulated, were identified after application of aspirin to cells at a 1/2 minimal inhibitory concentration (MIC). Gene Ontology (GO) analysis indicated enrichment in metabolic processes for the majority of the differentially expressed proteins. We then used the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database to analyse a large number of differentially expressed proteins and identified genes involved in biosynthesis of amino acids pathway, carbon metabolism (pentose phosphate and glycolytic pathways, tricarboxylic acid cycle) and nitrogen metabolism (histidine metabolism). These novel proteins represent candidate targets in aspirin-mediated inhibition of S. xylosus biofilm formation at sub-MIC levels. The findings lay the foundation for further studies to identify potential aspirin targets.